2013
DOI: 10.1371/journal.pone.0057461
|View full text |Cite|
|
Sign up to set email alerts
|

Amitozyn Impairs Chromosome Segregation and Induces Apoptosis via Mitotic Checkpoint Activation

Abstract: Amitozyn (Am) is a semi-synthetic drug produced by the alkylation of major celandine (Chelidonium majus L.) alkaloids with the organophosphorous compound N,N’N’-triethylenethiophosphoramide (ThioTEPA). We show here that the treatment of living cells with Am reversibly perturbs the microtubule cytoskeleton, provoking a dose-dependent cell arrest in the M phase. Am changed the dynamics of tubulin polymerization in vitro, promoted the appearance of aberrant mitotic phenotypes in HeLa cells and induced apoptosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Cell lysates were prepared as described previously [21]. Equal portions of protein (30 μg) were separated by SDS/PAGE, electrotransferred onto the nitrocellulose membrane and treated with the appropriate primary Ab diluted 1:1000.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared as described previously [21]. Equal portions of protein (30 μg) were separated by SDS/PAGE, electrotransferred onto the nitrocellulose membrane and treated with the appropriate primary Ab diluted 1:1000.…”
Section: Methodsmentioning
confidence: 99%
“…The semi-synthetic drug amitozyn was prepared as described previously at a concentration of 25 mg/mL [ 15 ]. CQ, pyrimethamine, ART, monoclonal mouse anti-α-tubuline (T9026), and polyclonal anti-γ-tubuline antibodies (T3559) were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Obtained results demonstrate that amitozyn possesses anti-malarial activity and inhibits in vitro blood stage growth of P. falciparum . Earlier, it has been shown that amitozyn is an effective anticancer drug, which acts as a microtubule modulator [ 15 ]. In this work the microtubule depolymerization effect of amitozyn was observed at different blood stages of P. falciparum, which could be the principal cause of its anti-malarial effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this case most of cancer cells died through apoptosis -the natural aging process. [5] Inherited resistance effect in rats race cured from Heren cancer was determined.…”
mentioning
confidence: 99%